Investor horizons and corporate policies under uncertainty - Christian Dreyer; Oliver Schulz (Review of Financial Economics, 2022)
In this study, we examine the differences in Investment, Employment, and Share repurchase sensitivities to uncertainty between firms with varying investor horizons. We test for these effects using two macro-based uncertainty measures (Baker et al., 2016; Ahir et al., 2018). The results show that in uncertainty times, greater short-term investor ownership is associated with less investment and hiring, and more net share buybacks. These findings are consistent with the preference of short-horizon investors of seeking to divest in the near future, thus, wanting to maximize current stock prices.
Keywords: 330; corporate policy; investor horizon; uncertainty